INJURY AND OSTEOARTHRITIS OUTCOME SCORE (KOOS) DI DESA MARO SEBO, KECAMATAN JAMBI LUAR KOTA, KABUPATEN MUARO JAMBI, PROVINSI JAMBI - Humaryanto; Patrick William Gading; Iskandar, Mirna; Justitia, Budi; Mulyadi, Deri (Universitas Jambi, 2024)
ABSTRACTOsteoarthritis (OA) is a musculoskeletal disorder caused by several changes as a result of metabolic disturbance. Primary OA is idiopathic, mainly degenerative, and occurs with age. Upon establishing the diagnosis of OA renders the condition itself to be irreversible, but it is possible to halt the progress of the current OA from reaching later and more debilitating stage. The knowledge and awareness of an individual to seek out treatment for potential OA and recognition of OA symptoms are therefore essential in catching the disease when it is still in the earler stages. Among the self-assessment tools available for the general public is the Knee Injury and Osteoarthritis Outcome Score (KOOS), which contains questions that assess the disability of caused by OA specifically of the knee joint. Desa Maro Sebo is a rural area where the majority of residents’ occupation is farming. Musculoskeletal complaints are quite prevalent and troublesome as their day-to-day productivity entails a high level of physical activity and mobility. Enhanced understanding in the symptoms of OA can improve earlier self-awareness about OA particularly of the knee. The method to achieve this is to introduce the KOOS questionnaire and demonstrate how it can be used as a tool for self-assessment by inviting at-risk members of the population to fill the questionnaire with each of their present conditions regarding their knee joints. This community service event was attended by 75 residents, ages 31 – 76 years old, with mean KOOS score of 76,68. The event proved that KOOS is a feasible self-assessment tool to be used for self assessment of symptoms of knee OA.Keywords: Osteoarthritis, self-assessment, knee injury, outcome score ABSTRAKOsteoarthritis (OA) adalah penyakit muskuloskeletal yang terjadi karena beberapa perubahan sebagai akibat dari gangguan metabolisme. OA primer terjadi secara idiopatik, sebagai penyakit degeneratif yang muncul karena penuaan. Apabila diagnosis OA sudah tegak maka OA tidak dapat disembuhkan, namun derajatnya dapat dihambat untuk tidak terjadi progresifitas ke derajat yang makin parah. Maka, peranan dari pengetahuan dan kewaspadaan individu masing-masing sangat penting dalam penilaian sendiri (self-assessment) mengenai kesehatan sendinya. Desa Maro Sebo terdiri atas warga dengan mata pencaharian utama masyarakatnya adalah bertani dan berkebun, maka keluhan nyeri muskuloskeletal adalah permasalahan yang dapat menghambat produktifitas kerja dan kualias hidup sehari-hari. Peningkatan pemahaman cara mengenai cara menilai kesehatan sendi lutut secara mandiri, salah satunya dengan memperkenalkan cara mengisi kuesioner KOOS, diharapkan dapat meningkatkan kewaspadaan warga untuk menghindari terjadinya atau memberatnya OA pada lutut. Metode yang digunakan untuk mencapai peningkatan pengetahuan ini adalah dengan mengundang masyarakat untuk memperkenalkan dan mendemonstrasikan cara mengisi kuesioner KOOS. Kegiatan pengabdian masyarakat ini dihadiri oleh 75 warga, dengan rentang usia 31 – 76 tahun, dan rata-rata skor KOOS 76,68. Kegiatan ini memperoleh simpulan bahwa penyuluhan kesehatan dengan memperkenalkan kuesioner KOOS cukup efektif dalam meningkatkan kesadaran dan pengetahuan masyarakat mengenai gejala awal yang dapat muncul karena penyakit OA, khususnya OA lutut.Kata kunci: osteoarthritis, penilaian diri, skor luaran, sendi lutut